Application of maximum dynamic strength training to improve acutely quick muscle action: a review of literature - Guilherme, João Paulo Limongi França (2012)
This study reviewed the physiological mechanisms and ways to implement maximum dynamics strength training for potentiate subsequent muscle actions carried out quickly, such as jumping or running on maximum speed. After the application of resistance exercise involving the maximum strength, molecular changes and alterations in motor recruitment by nervous system makes the exercise of quick strength become more efficient, a phenomenon known as post-activation potentiation. When performing this training method, the quick and maximum strength can be trained in one training session (microcycle), with both being optimized. After reviewing the more relevant publications on the subject, this paper proposes how to adopt this methodology in practice. The application of this method is important for athletes who use the quick strength on its modalities, such as soccer, basketball, volleyball and others or for those who wish to include this training within a certain stage in the assembly of your training program (periodization).